2009
DOI: 10.1016/j.ntt.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Developmental exposure to PCBs and/or MeHg: Effects on a differential reinforcement of low rates (DRL) operant task before and after amphetamine drug challenge

Abstract: The current study assessed the effects of developmental PCB and/or MeHg exposure on an operant task of timing and inhibitory control and determined if amphetamine (AMPH) drug challenges differentially affected performance. Long-Evans rats were exposed to corn oil (control), PCBs alone (1 or 3 mg/kg), MeHg alone (1.5 or 4.5 ppm), the low combination (1 mg/kg PCBs + 1.5 ppm MeHg), or the high combination (3 mg/kg PCBs + 4.5 ppm MeHg) throughout gestation and lactation. An environmentally relevant, formulated PCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 72 publications
12
44
0
Order By: Relevance
“…Some animal studies have reported sex-specific effects in rats exposed to PCBs. For instance, a previous study done in our lab found deficits on DRL15 performance in response to amphetamine following perinatal PCB exposure, and this effect seemed to be driven by poorer performance in males (Sable et al, 2009). The authors hypothesized that this sex difference may be due to PCB-induced reductions in aromatase activity (Hany et al, 1999), an enzyme responsible for the conversion of testosterone to estradiol, which may influence proper sexual differentiation of the brain as well as the proper development of the dopaminergic system in the prefrontal cortex of the developing male rat (Stewart & Rajabi, 1994).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Some animal studies have reported sex-specific effects in rats exposed to PCBs. For instance, a previous study done in our lab found deficits on DRL15 performance in response to amphetamine following perinatal PCB exposure, and this effect seemed to be driven by poorer performance in males (Sable et al, 2009). The authors hypothesized that this sex difference may be due to PCB-induced reductions in aromatase activity (Hany et al, 1999), an enzyme responsible for the conversion of testosterone to estradiol, which may influence proper sexual differentiation of the brain as well as the proper development of the dopaminergic system in the prefrontal cortex of the developing male rat (Stewart & Rajabi, 1994).…”
Section: Discussionmentioning
confidence: 74%
“…In one study using DRL15, rats exposed perinatally to the Fox River PCB mixture showed a lower ratio of reinforced to non-reinforced responses suggesting an impairment on this task (Sable et al, 2009). However, an earlier study found no significant effect of perinatal PCB treatment on DRL15 performance, although PCB-exposed rats did not extinguish lever pressing as readily as controls when tested on an extinction phase (Sable et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations